Peran Ketua Kelompok Wanita Tani dalam Pemanfaatan Lahan Pekarangan yang Berkelanjutan - Rindi Metalisa; Amiruddin Saleh; Prabowo Tjitropranoto (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2014)
The growing food needs become a significant issue due the population increases, farming lands converted, and climate change. One of attempt to support food needs is utilizing gardening that are environmental friendly and based on local resources. Optimizing gardening through women farmers group can be a huge potential in sustainability gardening. Therefore the role of women farm leaders is essential to direct their members toward this purpose. The objective of research was to analyze the influence of women farm leaders in gardening utilization. This research was conducted in Bogor through a survey method. Number of respondents was 75 people with a proportional simple random sampling technique. The data was collected in February to April 2014 and was analyzed using regression model. The result showed that gardening utilization sustainability was still similar with Food Consumption Acceleration Movement (P2KP) program, as seen from the types and number of plants. The role of women farm leaders that affect gardening utilization sustainability were motivators, and problem solvers. Groups leaders involvement in the utilization gardening can affect group members to maintain activities gardening post P2KP program. The role of groups leaders can be increased through extension activities, the use of communication media, and interact with other sources of information.Keywords: role, food needs, yard, women farmers